SAW generated electric charge on a metal disk on piezoelectrics - DANICKI, E. (Archives of Acoustics, 1990)
Scattering of a plane SAW by a circular, perfectly conducting disk on a piezoelectric halfspace is considered. A new theoretical approach allows to take into account the electric anisotropy of the substrate and gives the solution for the electric charge density on the disk in a form of fast convergent series for a wide range of wavelength of the SAW.